STRATEGI KESANTUNAN TINDAK TUTUR MAHASISWA KESEHATAN MASYARAKAT DALAM DISKUSI ILMIAH - Pujiati Tri; Gunawan Wawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This research is aimed to find out the polite utterance strategy of public health study program students, STIKES Kharisma Persada Pamulang, Tangerang Selatan.Theory of Brown and Leveinson (1987) and sosiopragmatics approach were used as analysis tools in finding out the polite utterance strategy of public health study program students.  Quantitave and qualitative method used to analyze the data which were taken from the students’ utterances.  The result of the research shows that (1) The used Politeness strategy : positive politeness strategy 63% and negative politeness strategy 37%. Overall, This research proves that the theory of Brown and Levinson can be used to find out the utterances politeness strategy used of students in discussion forum.